PENERAPAN PROBLM BASED LEARNING PADA MATERI HAND BOUQUET UNTUK MENINGKATKAN PERFORMA AKADEMIK MURID KELAS XI KECANTIKAN 1 SMKN 6 SURABAYA XI KECANTIKAN 1 SMKN 6 SURABAYA - Vika Nurul Izzah; Dewi Lutfiati; Nia Kusstianti; Mutimmatul Faidah (Jurnal Tata Rias, 2025)
The success of educational activities relies heavily on the use of innovative learning strategies. One such strategy is Problem-Based Learning (PBL), which emphasizes real-world and contextual problem-solving.This study aims to (1) evaluate the implementation of the PBL syntax, (2) analyze students’ academic performance covering intellectual (cognitive), behavioral (affective), and practical skills (psychomotor) dimensions, and (3) assess students’ responses to the application of PBL in the hand bouquet material. The research employed a quantitative approach with a pre-experimental design involving a single group that received a pre-test and post-test. The participants consisted of 32 eleventh-grade students from the Beauty Competency Group 1 at SMKN 6 Surabaya. Data collection instruments included observation sheets, academic tests, and questionnaires. Instrument validity was tested and confirmed to be valid. The reliability test yielded a Cronbach’s Alpha score of 0.991, indicating that the instruments were highly reliable and suitable for data collection purposes. The research data were analyzed using mean scores for the PBL syntax implementation and affective assessment, paired sample t-test for intellectual academic performance, one-sample test for practical performance, and percentage analysis for questionnaire data. The findings revealed that the PBL syntax implementation achieved an "excellent" category with a score of 4.88. Intellectual performance showed a significant improvement from a pre-test score of 57.66 to a post-test score of 82.19. The affective aspect improved from a score of 4.12 in the first session to 4.30 in the second, both falling under the "very good" category. Practical skill performance reached a score of 85.50, exceeding the minimum passing grade (KKTP) of 70. Students’ responses to the learning model were highly positive, with an average score of 96%. It can be concluded that the PBL model is effective in enhancing students’ academic performance in learning the hand bouquet material. Keywords: Pre-Experimental, Hand Bouquet, Problem-Based Learning